Participação dos receptores noradrenérgicos sobre as alterações motoras e neuroquímicas em um modelo experimental de parkinsonismo - Gois, Auderlan Mendonça de (2020)
PARTICIPATION OF NORADRENERGIC RECEPTORS ON MOTOR AND NEUROCHEMICAL CHANGES IN AN EXPERIMENTAL PARKINSONISM MODEL Introduction: Parkinson's disease (PD) is a multifactorial disease with no defined etiology and pathophysiology characterized by progressive death of dopaminergic neurons. However, evidence shows that noradrenergic dysfunction is associated with the progression of PD. Besides, epidemiological studies show that the use of β2-adrenergic agonists reduces the risk of PD. Therefore, this study aimed to evaluate the participation of noradrenergic receptors in response to the monoaminergic deficit induced by reserpine. Method: Wistar rats (6- to 8- month-old) were used. The animals were divided into six groups: control group (CTL); reserpine group (RES); salbutamol group (SALB); reserpine-salbutamol group (RES-SALB); propranolol group (PRO); and reserpine-propranolol group (RES-PRO). All animals received 12 subcutaneous injections of RES solution (0.1 mg/kg) or vehicle (CTL) throughout 25 days, one every 48 hours. After the 16th day (8th injection of RES), all animals were treated intraperitoneally with SALB (5 mg/kg), PRO (20 mg/kg) or vehicle for 8 days, one every 24 hours. The animals were submitted to behavioral tests of catalepsy I (performed every 48 hours, throughout the experiment), catalepsy II (performed on the 16th day - 30, 60, 120 minutes, 24 and 48 hours after the 1st injection of SALB and PRO), open field (performed on the 16th day, 60 minutes after the 1st injection of SALB and PRO) and oral movements (performed on the 16th day, 120 minutes after the 1st injection of SALB and PRO, on the18th and the 24th day). Forty-eight hours after the last injection of RES, the animals were anesthetized, perfused and the brains were submitted to immunohistochemical analysis of tyrosine hydroxylase (TH), dopamine β-hydroxylase (DβH) and α-synuclein (α-syn). Results: It was observed that a single injection of SALB and PRO attenuated the increase of oral movements such as vacuum chewing and tongue protrusion, induced by RES. On the other hand, repeated administration of SALB progressively reduced the time of catalepsy; and PRO attenuated the increase of oral movements (vacuum chewing and oral tremor) induced by RES. Regarding immunohistochemical analysis, it was observed that both SALB and PRO protected against the reduction of TH immunoreactivity in the substantia nigra pars compacta (SNpc), ventral tegmental area (VTA) and striatum, as well as for DβH in the locus coeruleus (LC); and against the increase of α-syn immunoreactivity in the substantia nigra pars reticulata (SNr), striatum, ventral subventricular area (VSA), CA1, CA3, dentate gyrus (DG) and medial prefrontal cortex (mPFC) caused by RES. Conclusion: Our results suggest that the modulation of RAβ promotes a neuroprotective effect on motor and neurochemical changes in the experimental model of parkinsonism induced by RES since an improvement in motor condition and an increase in TH and DβH immunoreactivity and a reduction of α-syn immunoreactivity in the experimental model of parkinsonism were observed.